Régimen Especial de los Procesos Contenciosos Tributarios en el Ecuador y su Integración en el Código Orgánico General de Procesos - Lascano Chávez, Diego Fernando (2016)
As a result of financial activity the tax system as a management activity to obtain public resources that will later be dedicated to works and services arises; but in this process of tax management mistakes by the central tax administration, branch and exception misapplication of substantive and adjectival rules misinterpretation of laws and regulations where the taxpayer is affected arise and as is an obligation to give affects the heritage of taxpayers, of the obligation so the state through public bodies has regulated the administrative claims to the administrator himself and contentious cases to the judiciary through the tax court. Keep in mind that the right to claim or sue not only is the Tax Code but also the Art. 173 of the Constitution empowers the challenge of any tax administrative act in administrative and contentious way. For this purpose we have established the procedural laws that constitute the way in which they have to travel those who believe affected. These procedures consisted in the Tax Code until May 22, 2016 and then have been incorporated into the Code of General Process it has done in the form inconsulta without taking into account the interest of the public entities and individuals for this arises this research to show that this special regulation of the Tax Code allowed the fulfillment of public purposes but being mesclados with in civil or private the public body that represents the people it is affected.